First Observations of Energy Budget and Bulk Fluxes at Ny Ålesund (Svalbard) during a 2010 Transition Period as Analyzed with the BEAR Station. (22nd May 2012) - Weill, Alain; Eymard, Laurence; Vivier, Frédéric; Matulka, Ania; Loisil, Rodrigue; Amarouche, Nadir; Panel, Jean Michel; Lourenço, Antonio; Viola, Angelo; Vitale, Vito; Argentini, Stefania; Kupfer, Heike
Abstract : A small-size meteorological mast, BEAR (Budget of Energy for Arctic regions) has been developed as a part of a new autonomous buoy for monitoring the sea ice mass balance. BEAR complements observations of the thickness and thermodynamic properties of the ice/snow pack determined by the so-called Ice-T (Ice-Thickness) buoy, giving access to bulk fluxes and energy budget at the surface, using meteorological measurements. The BEAR mast has been tested with success during ten days in April-May 2010 at Ny Alesund, in the Svalbard archipelago (Norway) showing that meteorological data were close to measurements at the same level of the Italian Climate Change Tower (CCT) from the ISAC-CNR. A discussion is undertaken on bulk fluxes determination and uncertainties. Particularly, the strategy to systematically use different relevant fluxes parameterizations is pointed out to explore flux range uncertainty before to analyze energy budget. Net radiation, bulk fluxes and energy budget are estimated using as average 10 minutes, 24 hours and the ten days of the experiment. The observation period was very short, but we observe a spring transition when the net radiation begins to warm the surface while the very small turbulent heat flux cools the surface.